Pengaruh Customer Relationship Management, Electronic Word of Mouth, dan Online Promotion terhadap Keputusan Pembelian pada Brand Make Up Wardah - Kadek Sinta Purnama Sari; I Gusti Ayu Imbayani; Made Pradnyan Permana Usadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of Customer Relationship Management (CRM), Electronic Word of Mouth (E-WOM), and Online Promotion on purchasing decisions for the Wardah make up brand. The research was motivated by fluctuations in Wardah’s sales performance during the 2020–2024 period amid intense competition within the cosmetics industry. This research applied a quantitative approach using a survey method with 112 respondents, who were followers of the Wardah Youth Ambassador Bali Instagram account and users of Wardah products. The sampling technique used was purposive sampling, while data were analyzed through multiple linear regression using the SPSS software. The findings reveal that Customer Relationship Management have a positive but not significant effect, meanwhile Electronic Word of Mouth, and Online Promotion each have a positive and significant effect on purchasing decisions, both partially and simultaneously. These results indicate that effective CRM strategies, positive online reviews, and consistent online promotions can increase consumers’ purchasing decisions toward Wardah make-up products.